Digital Transformation: How Information Systems Are Changing Traditional Business Models - Abelia Gultom Abel; Muhammad Irwan Padli Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
The evolution of information systems has emerged as a pivotal driver in the transition from traditional business models to modern, digitally oriented operations. Previously, companies largely depended on manual processes and direct interactions with customers, which often limited efficiency, scalability, and responsiveness. Today, the integration of information technologies, including e-commerce platforms, data management systems, and digital communication tools, enables businesses to operate more efficiently, make faster decisions, and maintain seamless interactions with a broader audience. This digital transformation empowers companies not only to expand their market reach but also to enhance operational effectiveness and strengthen customer relationships in meaningful ways. Moreover, the adoption of information systems influences the ways organizations create value, innovate, and maintain competitiveness in an increasingly globalized marketplace. This study explores the essential role of information systems in facilitating organizational change, highlighting their impact on business performance, strategic decision-making, and long-term sustainability. Understanding this dynamic is crucial for businesses seeking to thrive in the modern era, where technological integration is no longer optional but a fundamental component of growth and resilience.